11+10(x+10)=4-5(2x+11)

Simple and best practice solution for 11+10(x+10)=4-5(2x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+10(x+10)=4-5(2x+11) equation:



11+10(x+10)=4-5(2x+11)
We move all terms to the left:
11+10(x+10)-(4-5(2x+11))=0
We multiply parentheses
10x-(4-5(2x+11))+100+11=0
We calculate terms in parentheses: -(4-5(2x+11)), so:
4-5(2x+11)
determiningTheFunctionDomain -5(2x+11)+4
We multiply parentheses
-10x-55+4
We add all the numbers together, and all the variables
-10x-51
Back to the equation:
-(-10x-51)
We add all the numbers together, and all the variables
10x-(-10x-51)+111=0
We get rid of parentheses
10x+10x+51+111=0
We add all the numbers together, and all the variables
20x+162=0
We move all terms containing x to the left, all other terms to the right
20x=-162
x=-162/20
x=-8+1/10

See similar equations:

| n−3=1 | | 2=6-h | | -17=-2-5x | | 130-x=187 | | -2=v/20 | | 6x+8x+1-2=17 | | 8-13n=7n-12 | | m/4+2=7 | | -1/4(2y-6)=-10 | | 2(2x+1)+2(3x+2)=156 | | 3(w+1)-1=47 | | 7x+4(3x+2)=122 | | -5(7m-6)=-36-2m | | 5x+1+(5x+1)=92 | | -14y-28=-7(2y+4) | | –a/66+5=2. | | -1/2f=3 | | 3a/3=0/3 | | 6(w+3)=-2(w+31 | | F(x)=2x-10=-12 | | 1+x/4=-6 | | c+5/2=17 | | 28-y7y+4= | | 3/4m-2=-14 | | -3x-1=-4x+2 | | 61=3x-14 | | -5(3q-10)-5q=-15 | | -15=-1-7x | | 5(x-2)+1=3(x+4)+8 | | 5.7x-11.4=11.4 | | 5x-6=9x+5 | | -10=4(3x+1)-12x |

Equations solver categories